Factors influencing students' eating habits: The case of Ibn Tofaïl University, Morocco - Rektouti, Mohamed; El Bakkali, Mohamed; Bouchefra, Said; belomaria, Mohamed; Khal-layoun, Soad; Bour, Abdellatif (Acta Biomedica Atenei Parmensis, 2025)
Background: The transition to university life often disrupts students' eating habits, exposing them to unbalanced diets and health risks, particularly in developing countries like Morocco.Objective: This study aimed to identify sociodemographic, behavioral and nutritional determinants associated with meal regularity, fruit and vegetable consumption, and adoption of a balanced diet among students at Ibn Tofaïl University in Kenitra. Methods: A cross-sectional study was conducted between January 2021 and January 2024 among 1,036 undergraduate students aged 18 to 30. Data on dietary habits, sociodemographic characteristics and physical activity were collected via self-administered questionnaires. Multivariate logistic regression was used to identify factors associated with dietary behavior. Results : Female gender significantly increased the likelihood of regular meal frequency (OR = 2.66; p < 0.001) and fruit and vegetable consumption (OR = 2.19; p < 0.001). Self-preparation of meals was associated with greater meal regularity (OR = 2.27; p < 0.001) and adoption of a balanced diet (OR = 3.83; p < 0.001). A good knowledge of the principles of a healthy diet favored consumption of fruit and vegetables (OR = 1.99; p < 0.001) and following a balanced diet (OR = 2.25; p < 0.001). Consumption of traditional Moroccan dishes also increased the likelihood of adopting a balanced diet (OR = 1.34; p = 0.031). Conversely, the high cost of healthy foods was a significant brake on these behaviors (OR = 0.44; p < 0.001). Conclusions : Socio-cultural and behavioral factors play a key role in students' eating habits. Promoting autonomy in meal preparation, reinforcing nutrition education and improving accessibility to healthy, affordable foods could significantly improve university students' eating behaviors.